Non-contrast Magnetic Resonance Imaging versus the Multiphase Computed Tomography with Respect to the Asia–Pacific Clinical Practice Guidelines: A Diagnostic Performance Study for Liver Cancer - Wei, Yang; Haifen, Liu; Xiang, Li; Shutong, Zhang; Yanhao, Chen; Xiang, Wang (Turkish Journal of Gastroenterology, 2021)
Background: Guidelines recommend multiphasic computed tomography (CT) and/or contrast-enhanced magnetic resonance imaging(MRI) for the detection of hepatocellular carcinoma. The objectives of the study were to compare diagnostic parameters of non-contrastMRI against multiphase CT for diagnostic of hepatocellular carcinoma in patients who at risk of liver cancer considering Asia–Pacificclinical practice guidelines as the reference standard.Methods: Medical records of patients with chronic hepatic disease or have suspected liver cancer in surveillance of fewer than 100 daysand underwent multiphasic CT, gadoxetic acid-enhanced MRI, and liver biopsy for diagnosis of liver cancer were included in analysis.Enhancement during the arterial phase and wash-out during a delayed phase or portal-venous considered as hepatocellular carcinomain the multiphase CT. Mild-to-moderate hypersensitivity in imaging, presence of fat on out-of-phase imaging, non-enhancingcapsule(s), mosaic appearance, hemorrhagic content, and/or nodule-in-nodule considered as hepatocellular carcinoma in MRI. Asia–Pacific clinical practice guidelines considered for biopsy/histopathology for detection of hepatocellular carcinoma.Results: For detection of hepatocellular carcinoma, non-contrast MRI had higher sensitivity (0.843 vs. 0.762, P < .001, q = 3.919) andaccuracy (0.755 vs. 0.571, P < .001, q = 3.362) than the multiphase CT. While specificity was the same (0.864 vs. 0.809, P < .001, q = 2.584).Non-contrast MRI had 0-0.91 diagnostic confidence and multiphase CT had 0.49-0.81 diagnostic confidence for the detection of hepatocellularcarcinoma.Conclusions: Non-contrast MRI easily facilitates the decision of chemotherapy and/or radiotherapy than multiphase CT in hepatocellularcarcinoma.